Attitudes and behaviors toward Amazon River dolphins (Inia geoffrensis) in a sustainable use protected area - Mintzer, Vanessa J.; Schmink, Marianne; Lorenzen, Kai; Frazer, Thomas Kerry; Martin, Anthony Richard; Silva, Vera Maria Ferreira da (Biodiversity and Conservation, 2015)
Negative interactions between fishers and the Amazon River dolphin (Inia geoffrensis), or boto, have increased substantially in the last few decades. Herein, we investigate these interactions with focus on assessing fisher perceptions, attitudes, and behaviors toward botos. Moreover, we evaluate the effect that the Mamirauá Sustainable Development Reserve (MSDR) in the Brazilian Amazon, and related programs, has had on fisher attitudes and behaviors toward botos. The results suggest that interactions between fishers and botos, such as depredation and incidental entanglement, are frequent, and that the illegal harvest for botos, for use as bait, occurs in the majority of the study communities. However, the assessment revealed that most fishers have positive attitudes toward botos and that these attitudes have been influenced by participation in the MSDR activities such as research and ecotourism. Our results also highlight the importance of community-based enforcement in addressing the issue of boto harvesting. The MSDR programs have successfully promoted positive attitudes toward botos and have likely played a role in limiting boto mortality through behavioral controls, though the scope of influence of these programs has been restricted to a small geographical area. The current extent of these programs is insufficient to prevent the decline of the boto population; therefore, we suggest the MSDR model be used to improve and expand boto conservation efforts with communities in the region. © 2014, Springer Science+Business Media Dordrecht.
Keywords: Conservation Management; Dolphin; Environmental Management; Fishery Production; Local Participation; Perception; Protected Area; Sustainability; Amazon River; Inia Geoffrensis